2009
DOI: 10.1007/s00232-009-9207-z
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Calcineurin-Mediated Dephosphorylation in Modulation of an Inwardly Rectifying K+ Channel in Human Proximal Tubule Cells

Abstract: Activity of an inwardly rectifying K(+) channel with inward conductance of about 40 pS in cultured human renal proximal tubule epithelial cells (RPTECs) is regulated at least in part by protein phosphorylation and dephosphorylation. In this study, we examined involvement of calcineurin (CaN), a Ca(2+)/calmodulin (CaM)-dependent phosphatase, in modulating K(+) channel activity. In cell-attached mode of the patch-clamp technique, application of a CaN inhibitor, cyclosporin A (CsA, 5 microM) or FK520 (5 microM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…Moreover, Western blot analysis also revealed that CyA increased phospho-CaMKII, an active form of CaMKII (Gerges et al, 2005), as shown in Fig. 7 (Kubokawa et al, 2009). Taken together, these results strongly suggest that CaMKII-mediated phosphorylation suppresses channel activity, and CaN-mediated dephosphorylation reversibly elevates activity of the renal ATP-regulated K + channel.…”
Section: +supporting
confidence: 61%
See 4 more Smart Citations
“…Moreover, Western blot analysis also revealed that CyA increased phospho-CaMKII, an active form of CaMKII (Gerges et al, 2005), as shown in Fig. 7 (Kubokawa et al, 2009). Taken together, these results strongly suggest that CaMKII-mediated phosphorylation suppresses channel activity, and CaN-mediated dephosphorylation reversibly elevates activity of the renal ATP-regulated K + channel.…”
Section: +supporting
confidence: 61%
“…That is, CyA-induced channel suppression was blocked by a CaMKII inhibitor, KN-62, as shown in Fig. 6 (Kubokawa et al, 2009). Moreover, Western blot analysis also revealed that CyA increased phospho-CaMKII, an active form of CaMKII (Gerges et al, 2005), as shown in Fig.…”
Section: +mentioning
confidence: 76%
See 3 more Smart Citations